Studi Literatur: Skrining Fitokimia dan Aktivitas Farmakologi Tanaman Kelor (Moringa oleifera Lam) - Nur Amiiroh Isyraqi; Dewi Rahmawati; Yurika Sastyarina (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Indonesia has a wide variety of plants that can be used as medicinal ingredients. Biodiversity in Indonesia has a lot of potential as medicine so that it needs to be further explored regarding its properties for health. Moringa (Moringa oleifera Lam) belongs to the genus Moringaceae. Moringa plants have been widely used by the community as an herbal treatment to treat various diseases. The purpose of this study was to collect information related to phytochemical compounds and pharmacological activities of moringa plants using literature study methods. Literature search using appropriate keywords online using national and international indexed databases for the last 10 years (2010 to 2020). Based on the 18 literature that has been collected, the results obtained are chemical compounds identified in Moringa plants, including Alkaloids, Flavonoids, Saponins, Triterpenoids, Tannins, and Steroids. While the pharmacological activities found in moringa are antioxidant, anti-hyperuricemic, analgesic, anti-cancer, antihyperglycemic, anti-inflammatory, antihyperlipidemic, and antimicrobial activities.